Recent immigration raids increased student absences - Thomas S. Dee (Proceedings of the National Academy of Sciences, 2025)
Local immigration raids expanded dramatically across the United States during the first 2 mo of 2025. Anecdotal accounts suggest that these raids increased student absences from schools because parents fear being separated from their children. This study evaluates this claim using a daily time series of school absences spanning the current and two prior school years from five school districts serving communities subject to recent and unexpected raids in California’s Central Valley. The results indicate that recent raids coincided with a 22 percent increase in daily student absences with particularly large increases among the youngest students. These increased absences underscore the broader policy relevance of this immigration enforcement in terms of their impact on schools, childhood stress, and opportunities to learn.